Comparative study on differences of various agile methodologies and supporting tools in software maintenance - Nur Atiqah Mohamed Adanan, 1994-, author 611733 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains Komputer (Kejuruteraan Perisian))